Research on the homeostatic regulation of ecological fish tanks in human environment - Li Leijing; Li Fei; Li Ye; He Xingxin; Shen Han; Chen Fei; Wang Yongtao (E3S Web of Conferences)
Indoor fish tanks have become an important device for enriching the home environment and improving indoor ecology. In order to investigate the ecological homeostatic regulation of fish tanks under the combination of traditional fish culture and modern filtration systems, this study took a 35cm indoor ecological tank as the research object, conducted a 60-day comparative experiment (the first 30 days of traditional fish culture, and the second 30 days of the introduction of physical-biological filtration), and used the visual indicators such as water sensory, biological survival, and feeding efficiency of the grass carp as the evaluation criteria, and obtained the following conclusions: (1) The traditional method of fish culture is prone to water quality fluctuations in the early stage, and has high requirements for the density of organisms in the tank. (2) The use of filtration system is beneficial to stabilize the water quality and transparency, and enhance the feeding efficiency of the fish, but in the early stage of use, there will be the problem of releasing sedimentary material from the substrate disturbance. (3) The indoor eco-tank needs to balance the natural ecology and artificial regulation. The pursuit of ecological interest can choose the traditional method of fish culture, and the focus on ornamental stability is recommended filtration system. This study can provide a scientific basis for the configuration of aquarium environment and the maintenance of ecological system in the family human environment.